PENGEMBANGAN MEDIA VIDEO POWTOON SEBAGAI LAYANAN INFORMASI UNTUK DISIPLIN BELAJAR SISWA SMP DI BANJARBARU - Mega Pradina; Ani Wardah; Aminah Aminah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
In learning activities will not be separated from the rules and regulations that apply in schools. Students are required to be able to behave in accordance with the rules in force in the school, the importance of education in schools makes students realize that it is very important rules that must be obeyed. Discipline is an important issue in the learning process without discipline, students cannot follow good lessons. So far the teacher in general has provided guidance and counseling services through lectures, questions and answers, and advice. One effort that can be done by the teacher guidance and counseling is to use video powtoon as an alternative to convey information to students. In this study, researchers used R&D research, Media Information Services Development Using Video Powtoon for Student Learning Discipline adapted from the development strategy of Borg & Gall (in Sugiyono., 2018). Validation is done by counseling guidance experts, media experts, and user tests there are 4 aspects that are assessed namely the usefulness, feasibility, accuracy, and attractiveness. For the results of the video discipline assessment of learning discipline from counseling guidance experts, media experts, and user test researchers get the category